Case Report: Coexistence of Multiple Myeloma and Auricular Chondritis in VEXAS Syndrome - Matsumoto, Haruki; Fujita, Yuya; Fukatsu, Masahiko; Ikezoe, Takayuki; Yokose, Kohei; Asano, Tomoyuki; Tsuchida, Naomi; Maeda, Ayaka; Yoshida, Shuhei; Hashimoto, Honami; Temmoku, Jumpei; Matsuoka, Naoki; et al. (Frontiers in Immunology, 2022)
Vacuoles, E1 enzyme, X-linked, autoinflammatory, somatic (VEXAS) syndrome is an inflammatory disorder caused by somatic UBA1 variants, which are sometimes associated with hematological disorders, including myelodysplastic syndrome (MDS). VEXAS syndrome often overlaps with rheumatic diseases, including relapsing polychondritis. Here, we describe a case of VEXAS syndrome with auricular chondritis and exceptional multiple myeloma (MM). An 83-year-old man was diagnosed with MM, which was treated once by lenalidomide hydrate obtaining a partial response, but the patient did not desire further aggressive therapy. Although the treatment was effective, progressive macrocytic anemia and inflammation of both the ears emerged over the following 2 months. The histological examination of the auricle skin revealed that the perichondrial area was infiltrated by inflammatory cells, leading to the diagnosis of auricular chondritis. He was treated with oral prednisolone 40 mg/day, and his symptoms rapidly resolved. The re-evaluation of the histopathological bone marrow findings revealed vacuoles in the myeloid precursor cells without myelodysplasia-related changes. Sanger sequencing of UBA1 was performed using genomic DNA from peripheral blood leukocytes and revealed a somatic variant (c.122T>C:p.Met41Thr) consistent with VEXAS syndrome. This demonstrates that patients with chondritis can have complications with MM despite the absence of underlying MDS. A strong association exists between UBA1 variants and the risk of MDS; however, it remains elusive whether somatic UBA1 variants contribute to the development of plasma cell dyscrasia without MDS. Hence, we discuss the possible relationship between auricular chondritis and MM on a background of VEXAS syndrome.